Microbiological sampling and analyses in the food business operators’ HACCP-based self-control programmes - Aybar Espinoza, Mariel Stefhanie; Flink, Catarina; Boisen, Nadia; Scheutz, Flemming; Käsbohrer, Annemarie (Frontiers in Food Science and Technology, 2023)
A questionnaire was developed within the OH-HARMONY-CAP project providing an overview of current procedures for microbiological sampling and analyses in food business operators’ HACCP-based self-control programmes in EU/EEA countries. It focused on six bacterial species: Salmonella spp., Listeria monocytogenes, Campylobacter spp., Shiga toxin-producing Escherichia coli, Shigella spp. and Yersinia spp.; and five parasites: Trichinella spp., Cryptosporidium spp., Echinococcus granulosus (Sensu lato), Echinococcus multilocularis and Toxoplasma gondii. Participating EU/EEA countries distributed the questionnaire to food business operators’ laboratories within their countries and responses were received from nine countries. Feedback from 35 laboratories among 554 were considered for data analysis. Results showed that dairy products were analysed most frequently and the majority of laboratories analysed both ready-to-eat and non-ready-to-eat products. Laboratories analysing Salmonella spp. and Listeria monocytogenes processed the majority of samples. Accreditation for ISO-standards or an alternative method was in place in a considerable proportion of laboratories, but did not cover all pathogens investigated. Sending isolates for further confirmation to external laboratories was not common. In contrast, storing isolates was more frequently established. Around 60% of laboratories used more than one typing or characterisation method, predominantly MALDI-TOF, antimicrobial resistance typing and PCR, while 40% did not use any of these methods. Variability was observed as regards use of Whole Genome Sequencing; and participation in External Quality Assessment programmes. The study gathered insight into current practices of microbiological sampling and analyses performed in food business operators’ HACCP-based self-control programmes, and showed that further efforts are needed for harmonisation of analytical protocols and characterisation of foodborne pathogens.